Lana Del Reyâ€™s â€œOff to the Racesâ€ and Its Allusions to Vladimir Nabokovâ€™s Lolita - Mianani, Sindhy Sintya (Journal of Language and Literature, 2019)
No matter the era, ones always relate to the popular media whether it is literary words, song lyrics or movies. Yet, sometimes ones do not recognize the reference from a particular textual discourse swirling around them. From this premise,Â Â  Lana Del Reyâ€™s â€œOff to the Racesâ€ is deemed as the perfect example of this issue. Lana Del Reyâ€™s â€œOff to the Racesâ€ is an intriguing song, for its lyrics are said to have some relations to Vladimir Nabokovâ€™s Lolita. For her adaptation on Nabokovâ€™s Lolita, Del Rey has been attacked for ostensible discrepancies on who Lolita really is. Thus, this study attempts to prove the relation between Lana Del Reyâ€™s â€œOff to the Racesâ€ to Vladimir Nabokovâ€™s Lolita through Julia Kristevaâ€™s theoretical ideas on intertextuality. The discussion of this study indicates that, indeed, there is a relation between Lana Del Reyâ€™s â€œOff to the Racesâ€ to Vladimir Nabokovâ€™s Lolita. The lyrics of â€œOff to the Racesâ€ contains several lines and phrases indicating that Vladimir Nabokovâ€™s Lolita plays important role in its meanings. However, the some adaptations and reversal of the relationship between Lolita and Humbert in â€œOff to the Racesâ€ brings an entirely altered meaning to the song than the meaning in the original text.Keywords: intertextuality, lyrics, Lolita.